Die Begründer der Hamburgischen Wissenschaftlichen Stiftung - Gerhardt, Johannes (Mäzene für Wissenschaft, 2015)
According to a senior citizen of a trading company in Hamburg, if he is too stupid for sugar, let him study,"" Obviously, such an environment did not particularly appreciate science. Nevertheless, Senator Werner von Melle succeeded in collecting a sum of almost four million marks from many foresighted Hamburg citizens, so that the Hamburgische Wissenschaftliche Stiftung (Hamburg Scientific Foundation) was able to come into being on 12 April 1907. This first volume of the series ""Patrons for Science"" honours in short biographies all personalities who have been involved in the foundation's founding phase, either financially or through their participation on the board of trustees. Many of them have become well-known far beyond Hamburg, others have been completely forgotten.The book is introduced by the essay "Current Past" which embeds the founders of the foundation in the cultural and scientific-political context of Hamburg around the turn of the century. After its first publication in 2007, this volume is now in its 2nd edition completely revised and available in colour.